International law - Shaw, Malcolm N. (Malcolm Nathan), 1947- (Cambridge, UK ; New York : Cambridge University Press, 2008)
Malcolm Shaw's engaging and authoritative International Law has become the definitive textbook for instructors and students alike, in this increasingly popular field of academic study. The hallmark writing style provides a stimulating account, motivating students to explore the subject more fully, while maintaining detail and academic rigour. The analysis integrated in the textbook challenges students to develop
1. The nature and development of international law; 2. International law today; 3. Sources; 4. International law and municipal law; 5. The subjects of international law; 6. The international protection of human rights; 7. The regional protection of human rights; 8. Individual criminal responsibility in international law; 9. Recognition; 10. Territory; 11. The law of the sea; 12. Jurisdiction; 13. Immunities from jurisdiction; 14. State responsibility; 15. International environmental law; 16. The law of treaties; 17. State succession; 18. The settlement of disputes by peaceful means; 19. The International Court of Justice; 20. International law and the use of force by states; 21. International humanitarian law; 22. The United Nations; 23. International institutions.
economic&political bookfair2015
Includes bibliographical references and index.
Includes Web resources.
Keywords: International law